Overexpression of cytokinin dehydrogenase genes in barley (Hordeum vulgare cv. Golden Promise) fundamentally affects morphology and fertility - Mrízová, Katarína; Jiskrová, Eva; Vyroubalová, Šárka; Novák, Ondřej; Ohnoutková, Ludmila; Pospíšilová, Hana; Frébort, Ivo; Harwood, Wendy A; Galuszka, Petr (PLoS One, 2013)
Barley is one of the most important cereal crops grown worldwide. It has numerous applications, but its utility could potentially be extended by genetically manipulating its hormonal balances. To explore some of this potential we identified gene families of cytokinin dehydrogenases (CKX) and isopentenyl transferases, enzymes that respectively irreversibly degrade and synthesize cytokinin (CK) plant hormones, in the raw sequenced barley genome. We then examined their spatial and temporal expression patterns by immunostaining and qPCR. Two CKX-specific antibodies, anti-HvCKX1 and anti-HvCKX9, predominantly detect proteins in the aleurone layer of maturing grains and leaf vasculature, respectively. In addition, two selected CKX genes were used for stable, Agrobacterium tumefaciens-mediated transformation of the barley cultivar Golden Promise. The results show that constitutive overexpression of CKX causes morphological changes in barley plants and prevents their transition to flowering. In all independent transgenic lines roots proliferated more rapidly and root-to-shoot ratios were higher than in wild-type plants. Only one transgenic line, overexpressing CKX under the control of a promoter from a phosphate transporter gene, which is expressed more strongly in root tissue than in aerial parts, yielded progeny. Analysis of several T1-generation plants indicates that plants tend to compensate for effects of the transgene and restore CK homeostasis later during development. Depleted CK levels during early phases of development are restored by down-regulation of endogenous CKX genes and reinforced de novo biosynthesis of CKs.
Keywords: Hordeum; kořeny rostlin; Plant Roots; exprese genu; Agrobacterium tumefaciens; geneticky modifikované rostliny; cytokininy; fertilita; Fertility; Gene Expression; Plants, Genetically Modified; Oxidoreductases; Plant Proteins; oxidoreduktasy; ječmen (rod); rostlinné proteiny; Cytokinins